Antioxidant activity and phytochemical profiling of peaches, Arabica coffee, and their combination - Putri, Dhea Angela; Marsiati, Himmi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Antioxidant compounds scavenge unstable free radical reactions and are abundant in certain plants. Peaches (Prunus persica L.) are rich in phytochemicals such as carotenoids, anthocyanins, phenolic acids, and flavonoids, while Arabica coffee (Coffea arabica) contains alkaloids, flavonoids, tannins, steroids, and terpenoids. This study evaluated the antioxidant activity and phytochemical profile of peaches, Arabica coffee, and their combination using ethanol, ethyl acetate, and water as solvents. Extraction was performed via maceration with 96% ethanol and fractionation using water and ethyl acetate. Antioxidant activity was assessed using the DPPH (1,1-Diphenyl-2-picrylhydrazyl) assay, and phytochemical tests evaluated secondary metabolites such as alkaloids, flavonoids, phenolics, steroids/terpenoids, tannins, and saponins. Results indicated that the ethyl acetate extract of peaches showed moderate antioxidant activity (IC50 = 141.91 ppm), while the water extract of Arabica coffee exhibited robust activity (IC50 = 22.30 ppm). Notably, combining water extracts from both sources demonstrated enhanced antioxidant capacity (IC50 = 37.85 ppm), improving peach extract activity by over threefold. These findings underscore the potential synergistic effects of combining these natural sources for health-promoting antioxidants.